Immunomodulator Activity of the n-Hexane Extract of Binahong (Anredera cordifolia (Tenore.) Steenis) Leaves and Determination of Total Flavonoid Content - Perdana Priya Haresmita; Cut Dewi Bunga; Luluc Rianawati; Nisa Fitriyani; Nurkhayati Nurkhayati; Bilqis Rahil Azizah; Adi Hermawansyah; Missya Putri Kurnia Pradani (Jurnal Tumbuhan Obat Indonesia, 2025)
Binahong (Anredera cordifolia (Tenore.) Steenis) is one of the efficacious wild plants among us that has atherapeutic agent in the treatment of various diseases. This is influenced by secondary metabolite compoundsin the plant, especially flavonoids compounds. The purpose of this study was to determine theimmunomodulatory effect of n-hexane extract of Binahong leaves and determine total flavonoid contentcontained in Binahong leaves. The selected test animals were 25 mice divided into 5 different groups, eachgroup had 5 mice with a positive control, solvent control and a dose group of 25mg/kgBW, 50mg/kgBW and75mg/kgBW. One Way ANOVA test was used to compare immunomodulatory activity data with phagocytosiscapacity and phagocytosis index parameters. The research proved that n-hexane extract of Binahong leaves ata dose of 75mg/kgBW provided significant immunomodulatory activity with a significance value of p<0.05.The extract contains components of secondary metabolite flavonoid based on qualitative testing with colourreagents, namely FeCl3, NaOH and HCl with Magnesium (Mg) and the total flavonoid content was 3,370%calculated as quercetin. Keywords: Binahong, Immunomodulator, Macrophage, Phagocytosis, Total Flavonoid Content